Mediating Effect of Financial Behaviour on the Relationship Between Perceived Financial Wellbeing and Its Factors Among Low-Income Young Adults in Malaysia - Sabri, Mohamad Fazli; Wahab, Rozita; Mahdzan, Nurul Shahnaz; Magli, Amirah Shazana; Rahim, Husniyah Abd (Frontiers in Psychology, 2022)
The main objective of this study is to investigate the associations between financial knowledge, locus of control (LOC), and financial well-being (FWB) with financial behaviour as a mediator amongst young adults from low-income households in Malaysia. The sample of this study consisted of 520 young adults from five different zones in Peninsular and East Malaysia, which were selected using a multi-stage sampling technique. Data were collected using a set of questionnaire-based surveys. The data were then analysed using partial least square structural equation modelling. The study found that financial knowledge, both internal and external LOC, as well as financial behaviour, were significantly correlated with the FWB of low-income young adults in Malaysia. The results also revealed that financial behaviour mediates the associations between financial knowledge, internal and external LOC, and FWB. The findings of this study provide insights into the factors of FWB of low-income young adults in Peninsular and West Malaysia. Policymakers, government, and non-government organisations may utilise this study to develop new policies, financial programs, or campaigns to enhance the FWB of young adults in Malaysia.